The value of ∠EBD is 66°
<h3>Vertically opposite angles</h3>
Vertical angles are a pair of opposite angles formed by intersecting lines. Vertical angles are equal. Therefore,
∠EBA≅∠CBF
Therefore,
∠EBA = 40 - x
∠EBA + ∠EBD = 90°(complementary angles)
Therefore,
40 - x + 6x - 30 = 90
5x = 90 + 30 - 40
5x = 80
x = 80 / 5
x = 16
Therefore,
∠EBD = 6(16) - 30 = 66°
learn more on angles here: brainly.com/question/10987237
5cm, 471m, 464km... I hope that helped
Answer:
This is a statement not a question
Answer:
x³ - 6x² + 18x - 10
Step-by-step explanation:
(f - g)(x) = f(x) - g(x)
= x³ - 2x² + 12x - 6 - (4x² - 6x + 4)
= x³ - 2x² + 12x - 6 - 4x² + 6x - 4 ← collect like terms
= x³ - 6x² + 18x - 10
Answer:
The equivalent expression for the given expression
is
![4x^{3} y^{2}(\sqrt[3]{4xy} )](https://tex.z-dn.net/?f=4x%5E%7B3%7D%20y%5E%7B2%7D%28%5Csqrt%5B3%5D%7B4xy%7D%20%29)
Step-by-step explanation:
Given:
![\sqrt[3]{256x^{10}y^{7} }](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B256x%5E%7B10%7Dy%5E%7B7%7D%20%7D)
Solution:
We will see first what is Cube rooting.
![\sqrt[3]{x^{3}} = x](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7Bx%5E%7B3%7D%7D%20%3D%20x)
Law of Indices
![(x^{a})^{b}=x^{a\times b}\\and\\x^{a}x^{b} = x^{a+b}](https://tex.z-dn.net/?f=%28x%5E%7Ba%7D%29%5E%7Bb%7D%3Dx%5E%7Ba%5Ctimes%20b%7D%5C%5Cand%5C%5Cx%5E%7Ba%7Dx%5E%7Bb%7D%20%3D%20x%5E%7Ba%2Bb%7D)
Now, applying above property we get
![\sqrt[3]{256x^{10}y^{7} }=\sqrt[3]{(4^{3}\times 4\times (x^{3})^{3}\times x\times (y^{2})^{3}\times y )} \\\\\textrm{Cube Rooting we get}\\\sqrt[3]{256x^{10}y^{7} }= 4\times x^{3}\times y^{2}(\sqrt[3]{4xy}) \\\\\sqrt[3]{256x^{10}y^{7} }= 4x^{3}y^{2}(\sqrt[3]{4xy})](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B256x%5E%7B10%7Dy%5E%7B7%7D%20%7D%3D%5Csqrt%5B3%5D%7B%284%5E%7B3%7D%5Ctimes%204%5Ctimes%20%28x%5E%7B3%7D%29%5E%7B3%7D%5Ctimes%20x%5Ctimes%20%28y%5E%7B2%7D%29%5E%7B3%7D%5Ctimes%20y%20%20%20%29%7D%20%5C%5C%5C%5C%5Ctextrm%7BCube%20Rooting%20we%20get%7D%5C%5C%5Csqrt%5B3%5D%7B256x%5E%7B10%7Dy%5E%7B7%7D%20%7D%3D%204%5Ctimes%20x%5E%7B3%7D%5Ctimes%20y%5E%7B2%7D%28%5Csqrt%5B3%5D%7B4xy%7D%29%20%5C%5C%5C%5C%5Csqrt%5B3%5D%7B256x%5E%7B10%7Dy%5E%7B7%7D%20%7D%3D%204x%5E%7B3%7Dy%5E%7B2%7D%28%5Csqrt%5B3%5D%7B4xy%7D%29)
∴ The equivalent expression for the given expression
is
![4x^{3} y^{2}(\sqrt[3]{4xy} )](https://tex.z-dn.net/?f=4x%5E%7B3%7D%20y%5E%7B2%7D%28%5Csqrt%5B3%5D%7B4xy%7D%20%29)